Transcriptomic and protein expression analysis reveals clinicopathological significance of bloom syndrome helicase (BLM) in breast cancer - Arora, Arvind; Abdel-Fatah, Tarek; Agarwal, Devika; Doherty, Rachel; Moseley, Paul M.; Aleskandarany, Mohammed A.; Green, Andrew R.; Ball, Graham; Alshareeda, Alaa; Rakha, Emad; Chan, Stephen Y.T.; Ellis, Ian O.; et al. (American Association for Cancer Research, 2015)
Bloom syndrome helicase (BLM) has key roles in homologous recombination repair, telomere maintenance, and DNA replication. Germ-line mutations in the BLM gene causes Bloom syndrome, a rare disorder characterized by premature aging and predisposition to multiple cancers, including breast cancer. The clinicopathologic significance of BLM in sporadic breast cancers is unknown. We investigated BLM mRNA expression in the Molecular Taxonomy of Breast Cancer International Consortium cohort (n = 1,950) and validated in an external dataset of 2,413 tumors. BLM protein level was evaluated in the Nottingham Tenovus series comprising 1,650 breast tumors. BLM mRNA overexpression was significantly associated with high histologic grade, larger tumor size, estrogen receptor-negative (ER(-)), progesterone receptor-negative (PR(-)), and triple-negative phenotypes (ps < 0.0001). BLM mRNA overexpression was also linked to aggressive molecular phenotypes, including PAM50.Her2 (P < 0.0001), PAM50.Basal (P < 0.0001), and PAM50.LumB (P < 0.0001) and Genufu subtype (ER(+)/Her2(-)/high proliferation; P < 0.0001). PAM50.LumA tumors and Genufu subtype (ER(+)/Her2(-)/low proliferation) were more likely to express low levels of BLM mRNA (ps < 0.0001). Integrative molecular clusters (intClust) intClust.1 (P < 0.0001), intClust.5 (P < 0.0001), intClust.9 (P < 0.0001), and intClust.10 (P < 0.0001) were also more likely in tumors with high BLM mRNA expression. BLM mRNA overexpression was associated with poor breast cancer-specific survival (BCSS; ps < 0.000001). At the protein level, altered subcellular localization with high cytoplasmic BLM and low nuclear BLM was linked to aggressive phenotypes. In multivariate analysis, BLM mRNA and BLM protein levels independently influenced BCSS. This is the first and the largest study to provide evidence that BLM is a promising biomarker in breast cancer.